Drugs of abuse and stress increase the expression of GluR1 and NMDAR1 glutamate receptor subunits in the rat ventral tegmental area: common adaptations among cross-sensitizing agents - Fitzgerald, LW (J Neurosci, 1996)
Behavioral and electrophysiological evidence suggests that glutamatergic neurotransmission plays an important role in some of the long-term effects of cocaine and other drugs of abuse on brain function. We therefore examined the effect of repeated cocaine treatment on glutamate receptor subunit expression in central dopamine (DA) pathways implicated in many of cocaine's behavioral actions. By immunoblotting procedures using subunit-specific antibodies, we found that repeated, but not acute, cocaine treatment increased the levels of immunoreactivity of GluR1 (an AMPA receptor subunit) and NMDAR1 (an NMDA receptor subunit) in the ventral tegmental area (VTA), a nucleus containing mesolimbic DA neurons. In contrast, chronic cocaine treatment did not alter levels of GluR2 (an AMPA receptor subunit), NMDA2A/B (NMDA receptor subunits), or GluR6/7 (kainate receptor subunits) in this brain region. Moreover, GluR1 and NMDAR1 levels were not regulated in other regions of the mesolimbic or nigrostriatal DA pathways, including the substantia nigra. Because several drugs of abuse and stress can elicit common and cross-sensitizing effects on mesolimbic DA function, we next examined whether repeated morphine and stress treatments would regulate these proteins similarly in the VTA. Although morphine delivered by subcutaneous pellet implantation had no significant effect on subunit levels, morphine delivered intermittently by subcutaneous injections of escalating doses elevated GluR1 levels in the VTA. Repeated restraint stress also paradigm (2 stressors/d under variable conditions) increased both GluR1 and NMDAR1 levels in this brain region. Unlike cocaine, morphine, and stress, repeated treatment with other psychotropic drugs (haloperidol, raclopride, sertraline, and desipramine) that lack reinforcing or sensitizing properties did not regulate GluR1 or NMDAR1 subunit levels in the VTA. Increased glutamate receptor subunit expression in the VTA may represent an important molecular mechanism by which drugs of abuse and stress exert common, long-term effects on mesolimbic DA function.